Alternatives to paying child benefit to the rich: Means testing or higher tax? - Patricia Apps; Ray Rees; Thor Olav Thoresen; Trine Engh Vattø (Statistics Norway, Research Department, 2021)
The American Rescue Plan Act of 2021 implies that the US is effectively moving towards a general child benefit. However, the amount paid out is dependent on income, similar to schemes in several other countries. In the present paper, we argue that instead of suppressing the labour supply of middle income parents through withdrawing the transfer as a function of income, one should consider the obvious alternative of financing a generous universal child benefit by changing the overall income tax system. Implications of means testing relative to a tax financed universal alternative are discussed analytically in a piece-wise linear schedule. Moreover, we provide empirical illustrations of effects of child benefit design by combining information from behavioral and non-behavioral microsimulation models, representing the universe of Norwegian households. Results from both the analytical discussion and the simulations question the case for letting the child benefit be means tested.
Keywords: C25; J13; J22; 330; Child benefit design; Labour supply; Income distribution; piecewise linear tax schedule